Genome sequence of Picrophilus torridus and its implications for life around pH 0 - Fütterer, O. (National Academy of Sciences, 2004)
The euryarchaea Picrophilus torridus and Picrophilus oshimae are able to grow around pH 0 at up to 65°C, thus they represent the most thermoacidophilic organisms known. Several features that may contribute to the thermoacidophilic survival strategy of P. torridus were deduced from analysis of its 1.55-megabase genome. P. torridus has the smallest genome among nonparasitic aerobic microorganisms growing on organic substrates and simultaneously the highest coding density among thermoacidophiles. An exceptionally high ratio of secondary over ATP-consuming primary transport systems demonstrates that the high proton concentration in the surrounding medium is extensively used for transport processes. Certain genes that may be particularly supportive for the extreme lifestyle of P. torridus appear to have been internalized into the genome of the Picrophilus lineage by horizontal gene transfer from crenarchaea and bacteria. Finally, it is noteworthy that the thermoacidophiles from phylogenetically distant branches of the Archaea apparently share an unexpectedly large pool of genes.